The trailblazing life of Daniel Boone : and how early Americans took to the road - Harness, Cheryl (Harness, Cheryl. Cheryl Harness history., 2007)
Profiles the life and adventures of Daniel Boone; chronicling his childhood in Pennsylvania, service in the French and Indian War, journey across the Appalachians, and settlement of Boonesboro, Kentucky; and includes illustrations, maps, and primary source quotations.